Nitrogen fertilization of Cayman Blend grass (Urochloa hybrid cv. GP0423 + GP4467) on the chemical composition and fatty acid profile in milk from grazing cows - Acosta–Balcazar, Isabel Cristina; Bautista–Martínez, Yuridia; Estrada–Drouaillet, Benigno; Orzuna–Orzuna, José Felipe; Ruíz–Albarran, Miguel; Guiot–García, Jorge David; Granados–Rivera, Lorenzo Danilo (Revista Científica de la Facultad de Ciencias Veterinarias, 2025)
Conjugated linoleic acid (CLA) is a constituent of bovine milk that has been shown to possess protective effects against various diseases, including cancer. Therefore, there is a compelling rationale for increasing the content of CLA in milk. The feeding of cows in pastures has been demonstrated to increase CLA, as pastures typically have higher concentrations of linoleic and α–linolenic acids, which serve as precursors of CLA in the process of ruminal biohydrogenation. The enhancement of linoleic and α–linolenic acids can be achieved through management techniques that promote rapid vegetative growth, such as nitrogen fertilization. An experiment was conducted on a ranch in the state of Tabasco, Mexico, to determine the effect of nitrogen fertilization on the chemical composition and fatty acid profile of grass and bovine milk. The experimental design involved two plots, one of which was fertilized with urea (150 kg·ha-1), while the other served as a control. Each plot was assigned a group of five cows in production, utilizing a randomized complete block design. An intensive rotational grazing system was used, and grass and milk samples were taken on days 14, 21, and 28 of the experimental periods. Nitrogen fertilization of the grass increased (P≤0.01) more than 100% forage production and 15.75% the crude protein content in the grass. In milk, nitrogen fertilization of the grass increased (P≤0.05) the fat content by 31.68% but did not affect (P>0.05) the protein and lactose content or the content of CLA. A positive linear relationship was found (P≤0.05) between the concentration of linoleic acid in grass and the concentration of CLA in milk. The nitrogen fertilization of Cayman Blend grass increases forage production, the crude protein content in the grass, and the fat content in milk without affecting the content of conjugated linoleic acid and other fatty acids.